Orchestrating network control functions via comprehensive trade-off exploration - Bairley, Alan; Xie, Geoffrey G. (2016 IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN), 2016)
SDN orchestration, the problem of integrating and deploying multiple network control functions (NCFs) while minimizing suboptimal network states that can result from competing NCF objectives, is a challenging open problem. In this work, we formulate SDN orchestration as a multiobjective optimization problem, and present an evolutionary approach designed to explore the NCF tradeoff space comprehensively and avoid local optima. For an instance of the VM allocation problem subject to three independent NCFs optimizing network survivability, bandwidth efficiency, and power consumption, respectively, we demonstrate that our approach can enumerate a wider range of, and potentially better solutions than current orchestrators, for data centers with 100s of switches, 1,000s of servers, and 10,000s of VM slots.